Role of Vitamins in Human Health and Nutrition: Sources and Morbidity - C. Gupta, Umesh; C. Gupta, Subhas (Current Nutrition & Food Science, 2015)
Most vitamins were discovered accidentally when researchers were attacking specific diseases and not studying foods or medicine. For example, the disease “Beriberi” was prevented by eating unpolished rice (Oryza sativa). This was concluded to be due to the presence of thiamin also known as thiamine in the rice husk, which was later named as vitamin B1. If the diet is devoid of vitamin C, a deficiency disease called scurvy develops. If it is in the early stages, by eating foods; which contain Vitamin C, the person will be cured from the disease. Vitamins are organic substances, required in small amounts for body functioning and good health, which are found in the food we eat. Vitamins fall in two categories: water soluble and fat soluble. The water-soluble vitamins include 8 members of the vitamin B complex and Vitamin C; and vitamins A, D, E and K are fat soluble. If a particular vitamin is missing from the diet, the person will suffer from a deficiency disease. The human body can manufacture only a few vitamins. Some foods, e.g., bread and milk, are enriched, which means that vitamins are added. They are needed to help the body to use the energy nutrients, maintain normal body tissue, and act as a regulator. The best way for a healthy person to obtain needed vitamins is to eat a balanced diet. A daily diet of varied foods can provide needed essential vitamins for maintaining a healthy body. As an insurance to provide sufficient amount, vitamins in pill, liquid or capsule form can be taken as a supplement. Since water soluble vitamins are not stored in our body, they are excreted in urine; the supply of these vitamins should therefore be replenished daily to have sufficient amounts for human needs.
Keywords: dosage